Asking youth and adults about child maltreatment: a review of government surveys. Issue 11 (21st November 2022) - Campeau, Aimée; Tanaka, Masako; McTavish, Jill R; MacMillan, Harriet; McKee, Chris; Hovdestad, Wendy E; Gonzalez, Andrea; Afifi, Tracie O; Stewart-Tufescu, Ashley; Tonmyr, Lil
Abstract : Objectives: In this review we: (1) identify and describe nationally representative surveys with child maltreatment (CM) questions conducted by governments in low-income, middle-income and high-income countries and (2) describe procedures implemented to address respondents' safety and minimise potential distress. Design: We conducted a systematic search across eight databases from 1 January 2000 to 5 July 2021 to identify original studies with information about relevant surveys. Additional information about surveys was obtained through survey methods studies, survey reports, survey websites or by identifying full questionnaires (when available). Results: Forty-six studies representing 139 surveys (98 youth and 41 adult) conducted by governments from 105 countries were identified. Surveys implemented a variety of procedures to maximise the safety and/or reduce distress for respondents including providing the option to withdraw from the survey and/or securing confidentiality and privacy for the respondent. In many surveys, further steps were taken such as providing information for support services, providing sensitivity training to survey administrators when interviews were conducted, among others. A minority of surveys took additional steps to empirically assess potential distress experienced by respondents. Conclusions: Assessing risk and protective factors and developing effective interventions and policies are essential to reduce the burden of violence against children. While asking about experiences of CM requires careful consideration, procedures to maximise the safety and minimise potential distress to respondents have been successfully implemented globally, although practices differ across surveys. Further analysis is required to assist governments to implement the best possible safety protocols to protect respondents in future surveys.